The Influence of Psychological Empowerment and Psychological Safety on Lecturer Performance with Servant Leadership as a Mediating Variable - Latumahina, Jeffry; Syamsudin, Syamsudin; Joesah, Nurzalinar (Sean Institute, 2025)
This study examines the influence of psychological empowerment and psychological safety on lecturer performance, with servant leadership serving as a mediating variable. Using a quantitative approach, data were collected through purposive sampling from a group of university lecturers. The analysis employed Partial Least Squares Structural Equation Modeling to evaluate measurement and structural models. Findings indicate that both psychological empowerment and psychological safety significantly enhance lecturer performance, while servant leadership plays a pivotal mediating role in strengthening these effects. The results highlight that fostering a supportive work environment and empowering academic staff are crucial for improving performance in higher education. Theoretically, this research extends the understanding of human resource management in academic contexts, particularly the interplay between empowerment, safety, and leadership. Practically, the study offers recommendations for educational institutions to cultivate servant leadership and ensure psychological well-being to optimize lecturer contributions.